The Strategy Center Study of Regional Area to Center in Conflict of Placement of Ibukota District North Buton - Laode Muliawan (Journal of Local Government Issues, 2018)
The regional resistance to the center is a permanent issue that faithfully colors the history of the dynamics of central and local relations. This paper is a presentation of research results that try to express the opposition of Local Government to the Central Government which takes place in a closed form. Taking the case of the conflict in the capital of North Buton Regency, this research has succeeded in explaining that the resistance to the center by the regions is not always the case in an open form. Working out is a powerful strategy choice in reducing pressure and central intervention over the course of governance in the region.